2011
DOI: 10.1097/ana.0b013e3181f59db4
|View full text |Cite
|
Sign up to set email alerts
|

Deeper Total Intravenous Anesthesia Reduced the Incidence of Early Postoperative Cognitive Dysfunction After Microvascular Decompression for Facial Spasm

Abstract: Deeper total intravenous anesthesia can decrease the incidence of cognitive dysfunction in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…As a BIS value of 45 is generally regarded as the dividing line between “light” anesthesia and “deep” anesthesia, BIS values ranging from 30 to 45 are treated here as “deep” anesthesia and 45–60 as “light” anesthesia. This allowed for the target BIS values to be maintained for more than 80% of the total time from the induction to the cessation of anesthesia, as reported previously (An et al., ).…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…As a BIS value of 45 is generally regarded as the dividing line between “light” anesthesia and “deep” anesthesia, BIS values ranging from 30 to 45 are treated here as “deep” anesthesia and 45–60 as “light” anesthesia. This allowed for the target BIS values to be maintained for more than 80% of the total time from the induction to the cessation of anesthesia, as reported previously (An et al., ).…”
Section: Methodsmentioning
confidence: 85%
“…The choice of BIS targets for Deep and Light groups is based on previous studies. Two studies (An et al., ; Farag et al., ) defined lighter anesthesia as being a BIS target of 50–60 and deeper anesthesia as BIS target of 30–40. The underlying large‐scale randomize study (Short et al., ) which would recruite 6,500 patients with 40 to 50 centers internationally defined “light” anesthesia as a BIS target of 50 and “deep” anesthesia as a BIS target of 35.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns have been raised regarding how deeply individuals are anaesthetized and how this depth can affect post-anaesthetic behaviour (Culley et al 2004;Valentim et al 2008a;Valentim et al 2008b;Valentim et al 2010;Zurek et al 2012). Some studies have shown that Post-operative cognitive dysfunction was identified after light, but not deep, anaesthesia in humans (An et al 2011;Farag et al 2006). In mice, several studies showed that the anaesthetic that is most used in laboratory rodents, isoflurane, induces transient deficits of spatial memory (Culley et al 2004;Zurek et al 2012), especially when light anaesthetic depth is used (Valentim et al 2008a;Valentim et al 2010).…”
Section: Introductionmentioning
confidence: 99%